Saving Behavior among Undergraduate Students in Pathum Thani Province, Thailand - สีนาม, ฉัตรชัย; อภัยโส, ปิยะดา; สิงห์อุบล, ธิติพันธุ์; เชื้อเทวา, วรรธนะ; นาคเถื่อน, วิชุตา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to examine and compare the saving behavior of undergraduate students in Pathum Thani Province in terms of saving consistency, saving planning and goal setting, income allocation and expenditure control for saving, and tools and technologies that facilitate saving, classified by students’ personal factors. The sample consisted of 400 student representatives. Statistical analyses included percentage, mean, standard deviation, t-test, F-test, and pairwise comparisons using Scheffe’s method.            The findings revealed that undergraduate students demonstrated an overall moderate level of saving behavior. When considered by dimension, saving planning and goal setting ranked highest at a moderate level, followed by income allocation and expenditure control for saving, saving consistency, and tools and technologies that facilitate saving, respectively. The comparative analysis revealed that students from different faculties exhibited significantly different overall saving behaviors at the .01 level of statistical significance. Additionally, students with different residential statuses demonstrated significantly different overall saving behaviors at the .05 level of statistical significance.